A CLINICAL STUDY OF ECTOPIC PREGNANCY - Shaikh, Najma Bano; Shaikh, Shabnam; Shaikh, Farhana (Journal of Ayub Medical College Abbottabad, 2014)
Background: The frequency of ectopic pregnancy is increasing throughout the globe and it is the most life threatening emergency in first trimester of pregnancy. Objective of this study was to determine the frequency, risk factors, clinical presentation and management of ectopic pregnancy. Methods: This prospective descriptive study was conducted in Gynaecology and Obstetrical Unit-II of Liaquat University of Medical and Health Sciences Hospital Hyderabad from 1st May 2009 to 30th April 2012. All women diagnosed with ectopic pregnancy were included in the study. A predesigned pro forma was used to record the details about demographic features, pre-existing risk factors, clinical features at presentation and management of ectopic pregnancy. Data was analysed using SPSS-11. Results: Total numbers of admission during study period were 9600 with 60 cases of ectopic pregnancy, thus representing the frequency of 0.6% (1 in 160). Majority of women 43 (72%) were of 20-30 year age, multigravida 31 (52%) were the most sufferers. Pelvic inflammatory disease 27 (45%), previous abortion 20 (33%), previous surgery 12 (20%) were seen as common risk factors; however no risk factor was identified in 21 (35%) women. Typical history of amenorrhea and abdominal pain was found in 46 (77%) women, 23 (38%) were in a state of shock. Laparotomy was performed in 53 (88%) women. Three (5%) women were treated successfully with methotrexate. Laparoscopic surgery was done in 2 patients and 2 patients were required both Laparoscopy proceeded by laparotomy. No maternal death related to ectopic pregnancy was reported in our study. Conclusion: The early diagnosis of an ectopic pregnancy is one of the greatest challenges for obstetricians. The importance of early diagnosis lies in the fact that the lady can be offered a conservative line of management which can definitely have beneficial on her reproductive carrier. Keywords: Ectopic pregnancy, Pelvic inflammatory disease, Abortion, laparotomy, methotrexate